ANALISIS KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA MIO: Studi Kasus di Kelurahan Pejuang, Bekasi Barat - Angga Mustika Kurniawan, - (2019)
This study is a quantitative study aims to know the analysis of the quality product, the price, and the promotion toward buying decision. The population of this study is the society of district Pejuang, Bekasi Barat. The sample was conducted for 75 respondents. The methodology of this study is non-probability sampling, especially purposive sampling. The data was collected by distributing the questionnaire. This study analyzed using PLS (Partial Least Square) analysis technique. The result of this study showed that (1) the product quality significantly affect the buying decision with the coefficient percentage as big as 0,633. (2) the price significantly affect the buying decision with the coefficient percentage as big as 0,393. (3) the promotion did not significantly affect the buying decision with the coefficient as big as -0,052.